Business Intelligence to Optimize Decision-Making in a Telecommunication Company - Cano Lengua, Miguel Angel (2023)
This article presents an implementation of business intelligence in the sales area with the objective of optimizing decision-making in a telecommunications company because there is not good quality of reports and satisfaction in the use of reports is not suitable for correct decision-making due to the lengthy time it takes to do it manually, in addition, the quality is not optimal for data analysis. A Data Mart was developed under the Ralph Kimball methodology adapted to the agile Scrum methodology. Finally, software quality tests were carried out for BI implementation according to ISO/IEC 25010. The expected results were obtained regarding the improvement in report generation time of 97.22 %, an improvement in the data quality of the reports by 29.08%, an improvement in user satisfaction by 40% and finally, the perception in decision-making was optimized by 38.66%, according to the results it was concluded that business intelligence provides notable benefits regarding the quality of information, report generation time to make optimal decisions and improvement of decision making. For the telecommunications scenario, this research is important since, in the literature review, it is not observed papers that narrate the implementation of a business intelligence solution applied to the telecommunications sector.